Studying Consumers' Ecological Consciousness – A Comparative Analysis of Romania, Malaysia and Pakistan - Jamilah Ahmad; Imran Ali; Georgiana Florentina Grigore; Alin Stancu (Amfiteatru Economic Journal, 2012)
In the context of an increasing discourse on sustainability and environmental protection, the research on ecological consumer behavior becomes a necessity for companies. The extension in number of multinational companies determines an adaptation of their policies from one country to another. Based on a comparative approach of consumers in Romania, Malaysia and Pakistan, this paper analysis the dimensions of ecological consciousness, and highlights similarities and differences between the countries. In order to reach this objective, the research presents a structural equation model founded on primary data collected from an online survey. Religion and national culture are the main differences outlined by the analysis, in terms of ecological consciousness.
Keywords: O13; O57; 330; ecology; ecological consciousness; consumers; consumer behavior